2015
DOI: 10.1007/s40519-015-0214-z
|View full text |Cite
|
Sign up to set email alerts
|

Does when you eat and exercise matter? Differences in eating and physical activity patterns in overweight and obese adults

Abstract: This investigation found evidence that while eating patterns clearly contribute to daily energy intake on weekdays and weekends, they may not necessarily contribute to weight change. At the end of the day, what may be most important is regular self-monitoring and total caloric intake on both the weekdays and weekends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…In fact, these weekday-weekend dietary differences are present in adults as well. Not only do adults consume significantly more calories on weekends, but they also exercise less [ 30 , 31 , 32 , 33 , 34 ]. This unhealthy weekend lifestyle pattern contributes to weight gain and can even be detrimental to weight loss [ 31 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, these weekday-weekend dietary differences are present in adults as well. Not only do adults consume significantly more calories on weekends, but they also exercise less [ 30 , 31 , 32 , 33 , 34 ]. This unhealthy weekend lifestyle pattern contributes to weight gain and can even be detrimental to weight loss [ 31 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Not only do adults consume significantly more calories on weekends, but they also exercise less [ 30 , 31 , 32 , 33 , 34 ]. This unhealthy weekend lifestyle pattern contributes to weight gain and can even be detrimental to weight loss [ 31 , 34 ]. As habits are developed during childhood and maintained over time [ 35 ], it is critically important to understand more about how these eating patterns are established and factors that contribute to these differences.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, people with high PA expended more calories than people with low PA. This fact, together with a balanced diet, resulted in a clear weight loss [ 45 , 46 ]. In this regard, the current study found that the high PA group had more expended calories than the low PA group, which means a negative difference between ingested and expended calories.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, successful dieters are better prepared to navigate high-risk periods during their weight loss journey. Weekends and public holidays, known to pose challenges for individuals seeking weight loss [ 19 , 20 ], are particularly vulnerable times. Successful dieters demonstrate the ability to maintain their regular dietary habits and engage in compensatory behaviors, such as exercise, during these high-risk periods [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%